1998
DOI: 10.1002/(sici)1097-0061(199802)14:3<281::aid-yea212>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and disruption of the ARG8 gene encoding acetylornithine aminotransferase in the petite‐negative yeast Kluyveromyces lactis

Abstract: A recombinant plasmid was isolated from a Kluyveromyces lactis genomic DNA library which complements a Saccharomyces cerevisiae arg8 mutant defective in the gene encoding acetylornithine aminotransferase. The complementation activity was found to reside within a 2.0 kb DNA fragment. Nucleotide sequence analysis revealed an open reading frame able to encode a 423-residue protein sharing 68.1% and 35.0% sequence identities with the products of the ARG8 and argD genes of S. cerevisiae and Escherichia coli. That t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…It was closer to the Schizosaccharomyces pombe protein than to the S. cerevisiae one, Arg8p (encoded by YOL140w). Moreover, this sequence did not correspond to the K. lactis ARG8 gene product which has been cloned and whose disruption led to an arginine auxotrophic phenotype [28]. Analysis of the K. lactis genes which belong to this second category showed that the di¡erence between K. lactis and S. cerevisiae is not the presence/absence of orthologous genes but rather the presence/absence and the composition of gene families.…”
Section: Comparison With Other Organismsmentioning
confidence: 99%
“…It was closer to the Schizosaccharomyces pombe protein than to the S. cerevisiae one, Arg8p (encoded by YOL140w). Moreover, this sequence did not correspond to the K. lactis ARG8 gene product which has been cloned and whose disruption led to an arginine auxotrophic phenotype [28]. Analysis of the K. lactis genes which belong to this second category showed that the di¡erence between K. lactis and S. cerevisiae is not the presence/absence of orthologous genes but rather the presence/absence and the composition of gene families.…”
Section: Comparison With Other Organismsmentioning
confidence: 99%
“…S. cerevisiae genes were cloned by the complementation of S. cerevisiae mutants with S. cerevisiae plasmid libraries (Beggs, 1978;Hinnen et al, 1978;Hsiao and Carbon, 1979) and later genomic DNA libraries consisting of DNA fragments randomly inserted into yeast vectors using E. coli as a cloning host have been used for complementation cloning (Lundblad, 2001;Rose and Broach, 1991). Therefore, the cloning of genes into plasmid vectors was a common tool for gene manipulations in yeast as well as other species (Bergkamp et al, 1993;Janssen and Chen, 1998). In the present study, we demonstrate that the direct transformation of unmodified PCRamplified DNA is highly effective for the identification of auxotrophic genes in K. marxianus.…”
Section: Identification Of K Marxianus Auxotrophic Mutants With Genementioning
confidence: 99%
“…cerevisiae/E. coli shuttle vector pCXJ22 (Janssen and Chen 1998). Approximately 30 000 Ura + transformants were replica-plated on GlyYP and 10 respiration competent (Gly + ) colonies were scored after incubation at 30°C for 2 days.…”
Section: Isolation Of Klatp5mentioning
confidence: 99%